Idiosyncratic momentum on the JSE. Issue 3 (2nd July 2020) - Page, Daniel; McClelland, David; Auret, Christo
ABSTRACT: Idiosyncratic momentum, like price momentum, is a trading strategy that considers a share's recent relative performance over the short to medium term. Idiosyncratic momentum differs from price momentum as it uses residual returns post-orthogonalization on a single or multi-factor asset pricing model. Recent literature has shown that idiosyncratic momentum consistently outperforms price momentum on a risk-adjusted basis, is less prone to long-term reversal and has been proven successful in regions that have previously shown to have a non-existent price momentum premium. Previous studies attribute the success of idiosyncratic momentum to 'underreaction', whereby market participants tend to underreact to idiosyncratic momentum signals. We attempt to determine whether idiosyncratic momentum displays the same positive attributes found in international literature. We find that idiosyncratic momentum is superior to price momentum in terms of performance and explanatory power. The results reject a risk-based explanation of idiosyncratic momentum as minimising factor exposure (by using residual returns) improves performance. However, we find limited evidence of underreaction driving idiosyncratic momentum. Notwithstanding the lack of an a priori exposition of idiosyncratic momentum's existence, the results provide concrete evidence of idiosyncratic momentum's superiority over price momentum on the JSE, a finding important for both practitioners and academics alike.